2014
DOI: 10.1177/0042098014558541
|View full text |Cite
|
Sign up to set email alerts
|

Mapping producer services networks in mainland Chinese cities

Abstract: We analyse the geographies of urban networks created by leading producer services (PS) firms in China. Because of the national regulation of the Chinese state-led economy and the location strategies of global advanced producer services (APS) firms, the geography of global APS in China as examined by the Globalization and World Cities Research Network (GaWC) cannot be studied as a subnetwork of GaWC's global network, but needs an empirical study based on a wide range of leading PS in the Chinese market. We expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 63 publications
(104 reference statements)
0
60
0
1
Order By: Relevance
“…On the other hand, cities’ economic abilities decide their fixed (transport) infrastructure investments, and this in turn further facilitates intercity business connections and human flows. The fundamental role of cities’ economic size in shaping network formation has also been evidenced in the existing literature on mapping urban networks in mainland China: despite adopting varied lenses such as producer services, air passenger transport, high speed railways passenger flows and human intercity trips (Wang et al ; Liu et al ; Zhao et al ), economic centres are always found to be the most connected cities in these urban networks.…”
Section: Resultsmentioning
confidence: 88%
“…On the other hand, cities’ economic abilities decide their fixed (transport) infrastructure investments, and this in turn further facilitates intercity business connections and human flows. The fundamental role of cities’ economic size in shaping network formation has also been evidenced in the existing literature on mapping urban networks in mainland China: despite adopting varied lenses such as producer services, air passenger transport, high speed railways passenger flows and human intercity trips (Wang et al ; Liu et al ; Zhao et al ), economic centres are always found to be the most connected cities in these urban networks.…”
Section: Resultsmentioning
confidence: 88%
“…Spatial distribution modes of producer service sectors are influenced by a variety of factors of agglomeration and diffusion at different spatial scales by different industries [9][10][11][12]. In the early stage of development of metropolises, scholars studied the location characteristics of service industries from the perspective of accessibility, transaction cost, land rentals, and information services [13].…”
Section: Literature Review: Inner-city Locations Of Producer Service mentioning
confidence: 99%
“…Several empirical studies were conducted with the advent of city globalization after the 1990s. For example, scholars studied the decentralization conditions of different service sectors and office space at regional scales [14][15][16][17], and the connection pattern of producer service sectors between different cities [11,12]. In the inner scale of cities, changes in service sectors in different CBDs were discussed [12].…”
Section: Literature Review: Inner-city Locations Of Producer Service mentioning
confidence: 99%
“…Scholars have also examined the positions, trends, and prospects of key cities located in a specific region and particularly those of China in the world city network based on the interlocking networks of global advanced producer services (Brown, Catalano, and Taylor ; Derudder et al ; Hoyler ; Shi and Hamnett ; Taylor ; Taylor ; Taylor et al ). Furthermore, some scholars have started to map the producer services networks in a specific region based on a combination of global PS firms with a presence in the specific region as well as major domestic PS firms to show up more local cities (Beaverstock et al ; Yang and Yeh ; Zhao et al ).…”
Section: Introductionmentioning
confidence: 99%